The Role of Environmental Features of Parks in Activation of Recreational Activities in Leisure Time - Karim Zohrevandian; Ali Bastami; Hosein Naderloo; Ali Mohammad SafaNia (The Society of Aging and Physical Activity (SAPA), 2017)
Background. The recreational use of urban spaces has increased significantly in recent years, due to a trend towards healthier lifestyles in which regular exercise plays a leading role. Examples include walking, running or biking, activities for which large urban green parks provide excellent conditions. These parks, located within the city, are intended for public use and include landscape features such as trees, shrubs, extended grassy areas, playgrounds or water bodies. Objectives. The aim of this study was to investigate the role of environmental features of parks in activation of recreational activities. Methods. 425 people of over 18 years living near to six urban and regional parks in Tehran included in the study. Data collection has been done through questionnaire (Bedimo-Rung, 2005; Kaczynski, 2007 and Cohen, 2007), and data analysis has been done through structural equations and multivariate regression. Results. The research findings showed that the variables of design (t=2.84), green space (t=3.25), accessibility (t=2.17), Placement (t=3.18), beauty (t=2.04), traffic expectation (t=2.45), security (t=2.27), and management (t=2.35), have relation with attendance and attraction of users of parks for recreational activity. Conclusion. Management of public green spaces leads to increased presence and attendance of elderlies and recreational activities by creating building natural symbols and social interaction. Increased security of environment and its equipment leads to increased welfare, elevated revenues and occupational status and increased attendance of individuals in parks.